2020
DOI: 10.1002/star.201900306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystalline and Double Helical Structures on the Resistant Fraction of Autoclaved Corn Starch with Different Amylose Content

Abstract: The aim of this work is to investigate the effect of the crystalline and the double helical structures on the resistant starch (RS) fraction of autoclaved corn starch with different amylose content. Normal (NS) and high amylose (HS) corn starches are modified by autoclaving at 105, 120, and 135°C. Autoclaving causes structure disorganization in NS or structural rearrangements in HS. The RS increases from 2.1% to 5.5% in NS autoclaved at 135°C and from 12.7% to 30.2% in HS autoclaved at 120°C. The RS is correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…RS formation requires straight‐chain starches that can readily rearrange themselves into an ordered structure until they are closely aligned. The action of pronase allows the deconstruction of straight‐chain starch because the linear structures of straight‐chain molecules facilitate parallel orientation during regeneration, increasing the degree of crystallization and probability of RS formation (Soler et al., 2020). Aparicio‐Saguilán et al.…”
Section: Resultsmentioning
confidence: 99%
“…RS formation requires straight‐chain starches that can readily rearrange themselves into an ordered structure until they are closely aligned. The action of pronase allows the deconstruction of straight‐chain starch because the linear structures of straight‐chain molecules facilitate parallel orientation during regeneration, increasing the degree of crystallization and probability of RS formation (Soler et al., 2020). Aparicio‐Saguilán et al.…”
Section: Resultsmentioning
confidence: 99%
“…Double helix microcrystalline starch molecules have high thermal stability, which will lead to the increase of the content of RS (Figure 2). Using high‐pressure sterilization process to change the starch structure to control the resistance has a positive impact on the printing stability (Soler et al., 2020). Hot extrusion 3D printing mainly destroys the original crystal structure contributed by stacked double and single helices (Zheng, Tang, et al., 2022).…”
Section: Structural Characteristics Of Starches For 3d Printingmentioning
confidence: 99%
“…HMT modification increased the degree of order, degree of double helix, and relative crystallinity of the native LS, suggesting that the modifications increased the orderly arrangement of starch chains, which directly affected the crystallinity of starches and could promote the formation of the double helix. [65] Also, starch granules per unit area of modified starch increased owed to overlapping/infusion due to disruption of starch during hydrothermal processing and close 𝛾 -Irradiation Dosage-5, 10, 15, 20 kGy Amylose content and swelling power were decreased but solubility was increased by increasing the irradiation dose. SEM result revealed that at 5 and 10 kGy, the structure of starch granules was same but at 15 and 20 kGy, small alterations in structure was observed including roughness.…”
Section: Heat-moisture Treatment (Hmt) and Dry Heat Modification (Dhm)mentioning
confidence: 99%
“…Similarly, the increase in pasting temperature after HMT also corresponded to increased gelatinization temperature attributed to a reorientation of starch molecules and crystalline perfection. [ 65 ] These rearrangements reinforce intra‐molecular cross‐linking and bonding forces, requiring more heating temperature for structural breakdown and paste formation. However, “A” type crystalline pattern of native LS did not change to other patterns after the treatment.…”
Section: Modification Of Starchmentioning
confidence: 99%
See 1 more Smart Citation